Efektivitas Efektivitas Pemberdayaan Masyarakat Melalui Program Kewirausahaan Kelompok Usaha Bersama (KUBE) Oleh Dinas Sosial Kabupaten Bintan - Amalia, Dinda; Lestari, Andi Karmila; Sukmawati, Lilis (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2024)
The government has made various efforts to eradicate poverty. One of the efforts is to carry out community empowerment through an entrepreneurship program called a joint business group (KUBE). KUBE was formed with the aim of being able to reduce poverty through joint and cooperative efforts. In this research, measuring effectiveness is seen from several indicators, namely, target accuracy, program socialization, program objectives, and program monitoring. The aim of this research is to understand and analyze the effectiveness of community empowerment implemented through the Joint Business Group (KUBE) program in Sungai Lekop Village, East Bintan District, Bintan Regency. This research uses qualitative methods and the type of research is descriptive and data is obtained through direct interviews with informants and observation. The results of the research show that the effectiveness of community empowerment through the Joint Business Group Entrepreneurship (KUBE) program in Sungai Lekop Village, East Bintan District, Bintan Regency shows